2014
DOI: 10.1111/jsap.12281
|View full text |Cite
|
Sign up to set email alerts
|

Importance of fasting in preparing dogs for abdominal ultrasound examination of specific organs

Abstract: OBJECTIVE To describe the effect of fasting on the technical success of abdominal ultrasonography specifically in respect of examination of the gall bladder, duodenum, pancreas, adrenal glands and portal vein in dogs. METHODS Randomised, prospective study of 150 dogs with a variety of physical characteristics. Animals were divided into two groups of 75 dogs each. Dogs in Group 1 were fasted for 8 to 12 hours before ultrasonographic evaluation and those in Group 2 were not but received food anytime between 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…The length of fasting period used was based on the maximum fasting period suggested for rabbits [13], while avoiding gastrointestinal disorders. Fasting alone, as a method of preparation for abdominal ultrasound in rabbits, did not show better results than the controls as also shown for humans [8, 20] and dogs [21]. The combination of fasting and simethicone proved suitable to obtain mostly “acceptable” and “excellent” scores for images of the jejunum.…”
Section: Resultsmentioning
confidence: 80%
“…The length of fasting period used was based on the maximum fasting period suggested for rabbits [13], while avoiding gastrointestinal disorders. Fasting alone, as a method of preparation for abdominal ultrasound in rabbits, did not show better results than the controls as also shown for humans [8, 20] and dogs [21]. The combination of fasting and simethicone proved suitable to obtain mostly “acceptable” and “excellent” scores for images of the jejunum.…”
Section: Resultsmentioning
confidence: 80%
“…For a better sonographic approach, the animals were submitted to water and food fasts of six and 12 hours, respectively. However, Garcia & Froes (2014) in a study on preparing dogs for B scan and Doppler ultrasonography examination reported that there was no significant difference in image interpretation between animals that had fasted and those that had not. This information may be beneficial especially for critical patients that are under risk of complications in consequence of prolonged fasting, such as diabetic dogs and/or puppies.…”
Section: Discussionmentioning
confidence: 98%
“…Excessive intestinal gas and/or obesity are important reasons for misdiagnosis. Studies [25,26] showed that adjacent bowel gas is a factor contributing to the failure of ultrasound-guided procedures. In our study, four renal arteries were misdiagnosed during one RDU examination due to intestinal gas and/or obesity.…”
Section: Discussionmentioning
confidence: 99%